2021
DOI: 10.1007/s11356-021-13165-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of n-amyl alcohol/biodiesel blended nano additives on the performance, combustion and emission characteristics of CRDi diesel engine

Abstract: This paper deals with the study on the in uence of the effects of iron oxide nanoparticle additives when added to ternary fuel (diesel + Mahua methyl ester + Pentanol) on the emission, combustion and performance characteristics of a four stroke, single cylinder, common rail direct injection diesel engine working at a constant speed and varying operating scenarios. Doping is done in various proportions to the nanoparticle additives with the help of a homogenizer and ultrasonicator where the cationic surfactant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…It was observed that HC drops when there is a rise in NDR. It is due to a substantial amount of fuel oxidized owing to the fuel's nanoparticle content 35 . For all the load levels, an approximate decrease in HC of 5.5% and 9% for the NDR 25 ppm and NDR 50 ppm, respectively, were observed compared to HC registered for non‐doped diesel fuel.…”
Section: Resultsmentioning
confidence: 88%
“…It was observed that HC drops when there is a rise in NDR. It is due to a substantial amount of fuel oxidized owing to the fuel's nanoparticle content 35 . For all the load levels, an approximate decrease in HC of 5.5% and 9% for the NDR 25 ppm and NDR 50 ppm, respectively, were observed compared to HC registered for non‐doped diesel fuel.…”
Section: Resultsmentioning
confidence: 88%
“…10 Effect of heat release rate on nano-added diesel or biodiesel in Fig. 11D [193], the addition of iron oxide nanoparticles to the ternary fuel reduced the delay period as compared to pure diesel. The shorter delay period is attributable to improved atomization due to the high surface tension and calorific value of the blend.…”
Section: Ignition Delaymentioning
confidence: 96%
“…NP additives in nanofuels are known for their secondary atomization phenomena during combustion and their catalytic activity, which is often highlighted in engine performance tests [43,65,66]. Secondary atomization mechanisms are mostly related to particle concentration and the tendency of particles to form aggregates during combustion.…”
Section: Combustion Of G G/oa G/fementioning
confidence: 99%
“…Metal and metal oxide NPs have been extensively studied as potential metal fuel additives for diesel‐biodiesel blends, explosives, and pyrotechnics, with their catalytic activity and high oxygen content [1–6]. Aluminum, magnesium, lithium, bismuth, titanium, iron, tin, cerium, and their oxides have been investigated to accelerate oxidation, reduce ignition delay times and improve combustion rates [7–14].…”
Section: Introductionmentioning
confidence: 99%